Microwave absorbing properties of glass fiber/epoxy resin composites tailored with frequency selective surface based on nonwoven of carbon fibers metalized with nickel - Silveira, Daniel C. [UNESP]; Gomes, Newton A. S.; Rezende, Mirabel C.; Botelho, Edson C. [UNESP] (Springer Nature, 2020)
Radar absorbing structures (RAS) based on frequency selective surface (FSS) can be prepared to meet tailored properties in reducing electromagnetic interference in the microwave range, in addition to presenting mechanical properties suitable for structural applications. This article presents a study involving RAS processed by appropriate lamination and molding of glass fiber/epoxy resin prepreg and nonwoven of carbon fiber recovered with nickel and containing patterned unit cells to evaluate their electromagnetic behavior in X-band. The electromagnetic characterization shows good microwave attenuation results obtained by the RAS FSS with circular unit cells (maximum energy absorption of 89.8% at 12.2 GHz) and also with square unit cells (absorption of 82.8% at 12.3 GHz).